Biocontrol of Penicillium digitatum by native Bacillus and Pseudomonas strains isolated from orange peel - Ferreira, Flavia Vanina; Bello, Fernando; Rivadeneira, Maria Fernanda; Vazquez, Daniel Eduardo; Musumeci, Matías Alejandro (Elsevier, 2023)
Penicillium digitatum is a filamentous fungus that infects citrus fruits, causing decays that result in significant production losses. The application of synthetic fungicides is the main approach to control P. digitatum. However, intensive usage of fungicides has led to the proliferation of resistant P. digitatum strains. Besides, this practice poses a risk for the human and environmental health and is incompatible with organic markets. Alternative approaches that may overcome these limitations are valuable innovations for citrus production. The objective of this work was to evaluate the potential of bacterial strains inhabiting naturally in oranges to control the growth of sensitive and resistant to pyrimethanil P. digitatum strains. Around 50 bacteria were isolated from oranges peel but only three showed optimal antagonistic activity against sensitive P. digitatum after qualitative screening assays. These bacteria were identified by molecular and biochemical analyses and corresponded to Bacillus mojavensis SC-45, Bacillus velezensis SC-31 and Pseudomonas psychrotolerans SC-29. The antifungal activity of bacterial extracellular cultures against P. digitatum strains was quantified in vitro by the poison agar method and by measuring the mycelial growth at 600 nm in a microplate assay. B. velezensis SC-31 showed the highest growth inhibition of both P. digitatum strains. Lipopeptides with antifungal activity were identified by HPLC-ESI-MS in bacterial extracellular cultures. Surfactin and iturin were the most abundant lipopeptides produced by Bacillus spp., but higher yields were observed in B. velezensis SC-31 supernatant; whereas viscosin was mainly produced by P. psychrotolerans SC-29. B. velezensis SC-31 also showed the highest proteolytic activity and the highest capability to form biofilms. B. velezensis SC-31 and B. mojavensis SC-45 produced the lowest incidence and severity of disease in vivo after infection with both P. digitatum strains in preventive treatments. Besides, bacteria were compatible with concentrations of fungicides corresponding to maximum residue levels (MRL) on citrus fruits and higher concentrations used in drenches. B. velezensis SC-31 and B. mojavensis SC-45 are proficient antagonists to control green mould in oranges, which can be used together with fungicides to improve the inhibition of P. digitatum and avoid the emergence of resistant strains.